Ontology population and alignment for the legal domain : YAGO, Wikipedia and LKIF - Cardellino, Cristian (2017)
Fil: Cardellino, Cristian. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.